The process of developing a community-based research agenda with lesbian, gay, bisexual, transgender and queer youth in the Northwest Territories, Canada - Logie, Carmen; Lys, Candice (International Journal of Circumpolar Health, 2015)
This is an open access article published by Taylor and Francis Open in the International Journal of Circumpolar Health in 2015. Background. Youth in Canada’s Northwest Territories (NWT) experience sexual and mental health disparities. Higher rates of sexual and mental health concerns among lesbian, gay, bisexual, transgender and queer (LGBTQ) youth in comparison with heterosexual and cisgender peers have been associated with stigma and discrimination. Although LGBTQ youth in the NWTare situated at the nexus of Northern and LGBTQ health disparities, there is little known about their health, well-being and experiences of stigma. This short communication discusses the process of developing a LGBTQ youth community-based research programme in the NWT. Methods. We developed an interdisciplinary research team of LGBTQ and allied young adults, including indigenous and non-indigenous researchers, community organisers and service providers in the NWT. We conducted meetings in Yellowknife with LGBTQ youth (n 12) and key stakeholders (n 15), including faculty, students, community groups and health and social service providers. Both meetings included LGBTQ and allied participants who were LGBTQ, indigenous, youth and persons at the intersection of these identities. Results. LGBTQ youth participants discussed community norms that devalued same sex identities and stigma surrounding LGBTQ-specific services and agencies. Stigma among LGBTyouth was exacerbated for youth in secondary schools, gender non-conforming and transgender youth and young gay men. In the stakeholder meeting, service providers discussed the importance of integrating LGBTQ issues in youth programmes, and LGBTQ community groups expressed the need for flexibility in service delivery to LGBTQ youth. Stakeholders identified the need to better understand the needs of indigenous LGBTQ youth in the NWT. Conclusions. Community-based LGBTQ groups, researchers and health and social service providers are interested in addressing LGBTQ youth issues in the NWT. The emergence of LGBTQ community building, support groups and activism in Northern Canada suggests that this is an opportune time to explore LGBTQ youth health. This research was funded by a Canadian Institutes of Health Research (CIHR) Planning and Dissemination Grant- 0000303157.